Escrachos e Pussy Riot - Simões, Gustavo; Lucchesi, Flávia (Ecopolítica, 2013)
Texto e seleção de imagens por Gustavo Simões e Flávia Lucchesi. Acesso: http://www.pucsp.br/ecopolitica/galeria/galeria_ed5.html